Social cost benefit analysis of projects of a South African DFI, the Industrial Development Corporation - Tom, Lungile L (Research of GSB, 2018)
The need for social cost benefit analysis for appraising industrial projects by development finance institutions and developing economies has been seen to being relevant over the years and even since the 1960s. As such major global organisations, namely the United Nations Industrial Development Organisation (UNIDO), Organisation for Economic Cooperation and Development (OECD) and the World Bank have taken a step to sponsor research for developing practical methodologies for this purpose. It is quite evident that these organisations view social cost benefit analysis as a useful tool in project evaluation. These organisations have also issued various publications for this purpose. The first comprehensive methodologies for social cost benefit analysis were developed in the 1960s and this clearly provides the early rise of the usefulness and debate surrounding social cost benefit analysis. A study was performed in India in the early 90s where various projects from a state development finance institution were evaluated in order to conclude if a formal social cost benefit analysis was performed, would the projects been selected for investments by the state development finance institution. This research has been enthused by this Indian study as there is little to no research performed in the South African context for social cost benefit analysis in project evaluation. Previous literature from earlier years regarded the available methodologies for social cost benefit analysis as being too demanding in terms of the skill required as well as the information required for the performance. Over the years, UNIDO has developed software (COMFAR) in order to assist in the application of the methodology for social cost benefit analysis. This software has improved on the feasibility of performing social cost benefit analysis. This research follows the UNIDO Guidelines for Project Evaluation Methodology, which was also used in the Indian study. This methodology has also been incorporated in the COMFAR software. In summary, this research endeavours to conclude on whether there is any value in performing a formal social cost benefit analysis in project evaluation by DFIs.